Integrasi Desain Inklusif pada Perancangan Aplikasi Mobile Reminder Pengolahan Makanan bagi Ibu Menyusui - Erkamim, Moh.; Fitriyadi, Farid; Yulius, Rina (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
This study discusses the development of a mobile application called LactoMeal, which is specifically designed to assist breastfeeding mothers in organizing and processing food materials to meet the nutritional needs of both the mother and baby. The application was built using an inclusive design that adheres to WCAG accessibility standards. The SDLC prototype development model was chosen for use in this application because it allows for quick and flexible changes during the development process. To evaluate the usability of the application, this study used the System Usability Scale (SUS) with the participation of 51 users. The evaluation results showed an average SUS score of 71.127, indicating that the LactoMeal application is acceptable and has the potential to help breastfeeding mothers in organizing food materials. However, improvements are still needed in some aspects to enhance the quality of the application's usability.